Acquire and fire? Evidence from European mergers - Benjamin Furlan (University of Salzburg, Department of Social Sciences and Economics, 2015)
This paper provides a systematic analysis on the employment effects after merger and acquisition activities for a sample of European production firms. Rather than taking the perspective of the acquired firm, which has been extensively addressed in previous research, this paper focuses on the acquiring firm. At hand with a data set covering roughly 160.000 firms between 2003-2010 we apply propensity score matching methods to evaluate post-merger effects. Our results suggest that acquiring companies show a higher employment growth rate than their counterparts. This result holds by splitting our data in several sub samples (small and medium-sized firms, national takeovers).
Keywords: C; G; L; 330; merger and acquisition evaluation; propensity score matching; employment effects